Analisis Pembayaran Premi Pada Asuransi Syariah (Studi Kasus di PT. Sunlife Cabang Medan) - Hafnisa, Hafnisa; Syahriza, Rahmi (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to analyze the calculation model of insurance premium rates of savings and non-savings products against market segmentation and profitability. This research method uses qualitative descriptive. Regarding the characteristics of savings products, it is more appropriate to apply them to individual segmentation, while non-deposit products are more appropriate if they are marketed to groups or companies. Companies that invest at a high rate of return will use relatively less debt. A high rate of return will allow them to finance most of the finances when they need funds collected from internal activities.